(untitled) (Fiep Bulletin - online, 2014)
The propose of this work is to compare the capacity to jump from the Squat Jump (SJ) and Countermovement Jump (CMJ) techniques in the collective sports of blocks volleyball, handball and futsal. The performance in the SJ is a criterion to measure the concentric force and through the relation it enters the heights in the SJ and CMJ, is possible to evaluate the elastic capacity of the muscle, as well as the exploitation of the "Principle of the Initial Force", according to this principle, the preparation movement is carried through in the contrary direction to the main movement that cause, a bigger initial force at the moment of the inversion of the direction of the movement, that it is the beginning of the main phase. The sample of citizens was composed for 34 individuals of the masculine sex being 11 athletes of volleyball, 11 of handball and 12 of futsal. The results of the comparison of the income between SJ and CMJ of each modality had inside shown that it had differences in volleyball and futsal. This indicates that these athletes use the principle of the "Initial Force", as well as of the muscle coordination. The differences of the averages of the jumps between the modalities demonstrate that the players from volleyball jump more than from handball and the futsal, when used the CMJ. This can be explained by the fact that in volleyball the jump is present in a great part of the inherent techniques to this disciplines porting. However, it did not have significant differences for the SJ. This can be explained by the fact of this jump technique is not common for the studied modalities.